(untitled) (Cadernos de Filosofia Alemã: Crítica e Modernidade, 1997)
This paper deals with the Declaration of Fichte’s Doctrine of Science, Kant’s objection to Fichte published in 1799. The first part of the text tries to determine the historical horizont of theDeclaration by presenting some biographical data about Kant’s relations with disciples (especially with Fichte). In the second part, some reasons are pointed out to justify, from the point of view of the Critique of Pure Reason, Kant’s defense against Fichte’s interpretation of that work. Finally, this controversy, which involves a comparison between Kant’s philosophy and Fichte’s, leads us to some questions about the pertinence of the method used by some authors to interpretate the relation between that two philosophical systems.